Analysis of Fu Caiyun's “dissolute beauty” and Zeng Pu's “struggle between two minds” ：a study based on Bakhtin's polyphony in perspective - Zhiqin, Li; Chin, Mooi San (Universiti Pendidikan Sultan Idris, 2024)
Fu Caiyun, the Reckless Beauty ””, is the most complex artistic character created by Zeng Pu in Sinful Sea F l owers, which has received mixed reviews from academics. The reason for the controversy is the obvious polyphony of Sinful Sea Flowers. Zeng Pu does not narrate Fu Caiyun's story with the absolute authority of the author, Fu Caiyun has a subjective position in the novel , and she expresses her own voice and forms a double subject dialogue with the author Zeng Pu's voice. Thus Fu Caiyun becomes a Reckless beauty with polyphonic characteristics in Sinful Sea Flowers. The polyphony of Reckless Beauty is the result of Zeng Pu's two minds struggle with the historical and cultural context in which he lives . The blending of new and old identities, the cultural dialogue between Chinese and Western influences are internal conflicts that impacted Zeng Pu' s rewriting of Fu Caiyun, rendering her character with a polyphonic nature of multiple voices. The text is filled with dialogues between Zeng Pu's self ””' and the other Fu Caiyun. Essentially, this represents a double voiced polyphony of Zeng Pu's consci o us and unconscious minds, embodying the struggle between two minds within his internal subjective world.